Estudio descriptivo de la movilidad sagital raquídea global y segmentaria en bailarinas de flamenco - Sebastián Gómez-Lozano; Alfonso Vargas-Macías; Fernando Santonja Medina; Manuel Canteras Jordana (Revista del Centro de Investigación Flamenco Telethusa, 2012)
The purpose of this study was to determine the global and segmental trunk mobility (dorsal and lumbar rachis) in a sample of female flamenco dancers. The material and method consisted of quantifying with an inclinometer the mobility sagittal of the spine. The variables analyzed have been the range of movement of the flexion and extension of the rachis on a segmental basis in the thoracic and lumbar vertebra and in the trunk as a whole. The participants in the study were 66 volunteers, 33 female flamenco dancers (22.12 ± 4.21 years old, 162 ± 5.35 cm y 53.5 ± 4.07 Kg) and a control group of 33 women (22.71 ± 3.23 years old, 164.12 ± 4.87 cm and 55.51 ± 5.68 kg). The statistical method was a descriptive study. The comparison between the groups was done with the t test student. The flamenco dancers showed greater global trunk flexibility than the control group, in maximum flexion (162.21º ± 8.1º to 141.10º ± 9.8º), maximum extension (90.81º ± 12º to 79.06º ± 9.04º) and full mobility (253.03º ± 17.05º to 220.87º ± 15.74º). Regarding the lumbar rachis, the maximum flexion results were similar between the dancers and the control group (55.60º ± 8.04º and 56.15º ± 7.68º respectively), however the dancers had greater extension (44.51º ± 9.37º to 30.06º ± 12.42º) and complete mobility (100.12º ± 11.79º to 85.94º ± 11.31º). Finally, the dorsal rachis results were also variable: the maximum flexion of the dancers was higher (30.18º ± 8.28º to 21.36º ± 9.79º) while their dorsal extension was lesser (16.12º ± 7.93º to 23.15º ± 8.65º) and there were no significant difference in the dorsal rachis (46.30º ± 6.67º for dancers and 44.51º ± 7.58º for non-dancers). These results reflect how the practice of flamenco dancing improves the global mobility of the spine, in both maximum flexion and extension, due to the morpho-functional adaptations characteristic of the style. This improvement is also evident in local studies of the dorsal and lumbar areas of the back, except in the maximum extension of the dorsal rachis which shows a lower range of mobility, possibly due to a straightening of the degree of spinal curvature characteristic of female flamenco dancers.